2017
DOI: 10.1021/acschembio.7b00649
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of DNA Binding and Cas3 Recruitment by the CRISPR RNA-Guided Cascade Complex

Abstract: Bacteria and archaea rely on CRISPR (clustered regularly interspaced short palindromic repeats) RNA-guided adaptive immune systems for sequence specific elimination of foreign nucleic acids. In Escherichia coli, short CRISPR-derived RNAs (crRNAs) assemble with Cas (CRISPR-associated) proteins into a 405-kilodalton multi-subunit surveillance complex called Cascade (CRISPR-associated complex for antiviral defense). Cascade binds foreign DNA complementary to the crRNA guide and recruits Cas3, a trans-acting nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…2 and Majumdar et al 2015) and as was previously observed in Sulfolobus islandicus (Peng et al 2013) and Thermoproteus tenax (Plagens et al 2012, 2014), the Cas3′ and Cas3″ polypeptides of differing Type I-A systems are integral structural components of the effec- tor crRNPs that target destruction of invader DNA. In con- trast, the single Cas3 subunit of other systems acts in trans with the effector crRNP and only becomes recruited and activated for function upon crRNP-target DNA interaction and crRNA-induced R-loop formation of the target DNA (Elmore et al 2015; Hayes et al 2016; Jackson et al 2014; Mulepati et al 2014; van Erp et al 2015, 2018; Wang et al 2016; Xiao et al 2018; Zhao et al 2014). In this study, we reconstituted functional Pfu Type I-A crRNPs that cleave double-stranded DNA targets in a PAM (5′-GGG/CCN-3′) and crRNA-dependent manner (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…2 and Majumdar et al 2015) and as was previously observed in Sulfolobus islandicus (Peng et al 2013) and Thermoproteus tenax (Plagens et al 2012, 2014), the Cas3′ and Cas3″ polypeptides of differing Type I-A systems are integral structural components of the effec- tor crRNPs that target destruction of invader DNA. In con- trast, the single Cas3 subunit of other systems acts in trans with the effector crRNP and only becomes recruited and activated for function upon crRNP-target DNA interaction and crRNA-induced R-loop formation of the target DNA (Elmore et al 2015; Hayes et al 2016; Jackson et al 2014; Mulepati et al 2014; van Erp et al 2015, 2018; Wang et al 2016; Xiao et al 2018; Zhao et al 2014). In this study, we reconstituted functional Pfu Type I-A crRNPs that cleave double-stranded DNA targets in a PAM (5′-GGG/CCN-3′) and crRNA-dependent manner (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…PAM recognition by the surveillance complex destabilizes the DNA duplex and facilitates crRNA-guided strand invasion 22,35,36 . Hybridization of the crRNA-guide to the complementary DNA displaces the non-complementary strand, resulting in an Rloop structure [35][36][37][38][39][40][41][42] . The N-terminal domain of Cas8f and the opposing face of the terminal Cas7f subunit (Cas7f.6) form a positively charged "vise" that closes around dsDNA ( Figure 2B-C) 22,24 .…”
Section: Cas8f Mediates Dsdna Binding and Pam Recognitionmentioning
confidence: 99%
“…In this work, we took the cas3 gene as a target to study genome engineering in Z. mobilis, and different cas3 mutant strains were successfully obtained. All Type I systems use a complex of Cas proteins to bind to a target while employ Cas3 nuclease to execute protospacer cleavage (63,64).…”
Section: Discussionmentioning
confidence: 99%